What causes Ngancar River in Wiroko Temon sub-watershed vulnerable to flooding?. Issue 1 (September 2021) - Prastica, R M S; Fanani, A J
Abstract: The vulnerability to flooding becomes a concern in every region to optimize the mitigation strategy, hence the disaster impact can be reduced from the environment. What factors become the main triggering issue toward water-related disasters? Every region has a different answer. Can a river that does not have historical flood events become vulnerable to flood today? This study investigates the flooding factors in Ngancar River, Wiroko Temon sub-watershed, Wonogiri. The research employs hydrological and hydraulics analysis. The results reveal that Ngancar River experienced land-use changes over time which lead to the dynamic of the discharge return period being bigger. As a result, river capacity today cannot accommodate the flooding volume. The research concludes that the hydraulics condition needs to be improved for flood mitigation. Further hydrological analysis is suggested to be conducted.